Clinical evaluation of a barrier cream in periwound skin management. Issue 3 (2020) - Nair, Harikrishna KR; Chong, Sylvia SY; Kamis, Siti Aishah Binti; Zakaria, Ahmad Muhaimin Bin
No abstract available